2011
DOI: 10.1038/labinvest.2011.1
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of SERPIN B3 promotes epithelial proliferation and lung fibrosis in mice

Abstract: SERPIN B3/B4, members of the serpin superfamily, are fundamental for the control of proteolysis through a known inhibitory function of different proteases. Several studies have documented an important role of SERPIN B3 in the modulation of inflammation, programmed cell death and fibrosis. To confirm the role of SERPIN B3 in lung fibrosis and overall investigate its influence on epithelial dysfunction, a stratified controlled trial randomly assigning bleomycin (BLM) treatment was performed on both SERPIN B3 tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 34 publications
1
46
0
Order By: Relevance
“…Idiopathic pulmonary fibrosis (IPF) lung samples wherein more extensive fibrosis was observed in patients with higher SERPINB3/B4 expression (Calabrese et al, 2008). Furthermore, it has confirmed that SERPINB3 plays role in inhibiting inflammation and favoring epithelial proliferation with increased TGF-β secretion and thus the likelihood of consequent fibrogenesis (Lunardi et al, 2011). DKK1, a secreted protein, controls Wnt signaling by binding the lung resistance-associated protein coreceptor and sterically blocking Wnt binding to the receptor complex (Bafico et al, 2001;Mao et al, 2001).…”
Section: Discussionmentioning
confidence: 95%
“…Idiopathic pulmonary fibrosis (IPF) lung samples wherein more extensive fibrosis was observed in patients with higher SERPINB3/B4 expression (Calabrese et al, 2008). Furthermore, it has confirmed that SERPINB3 plays role in inhibiting inflammation and favoring epithelial proliferation with increased TGF-β secretion and thus the likelihood of consequent fibrogenesis (Lunardi et al, 2011). DKK1, a secreted protein, controls Wnt signaling by binding the lung resistance-associated protein coreceptor and sterically blocking Wnt binding to the receptor complex (Bafico et al, 2001;Mao et al, 2001).…”
Section: Discussionmentioning
confidence: 95%
“…SerpinB3 inhibits several types of proteases and plays a role in modulating inflammation, programmed cell death and fibrosis [27]. S100A8 and S100A9 proteins, so called calgranulins, are known for their antimicrobial activity and their role as pro-inflammatory mediators in acute and chronic inflammation [28][30].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, SerpinB3 and Uteroglobin decreased exclusively in young non-susceptible individuals, and ELISA experiments confirmed this for SerpinB3. The differential SerpinB3 and Uteroglobin response on smoking between the two young groups suggests that these proteins might be crucial for the very first steps towards COPD, given its modulatory function in inflammation and fibrosis [27] and release of lysosomal proteinases from damaged epithelial cells [34]. SerpinB3 concentrations have been shown to be higher in bronchoalveolar lavage fluid of smokers than non-smokers [35].…”
Section: Discussionmentioning
confidence: 99%
“…24 By immunohistochemistry SERPINB3 protein was documented in transgenic animals in the hepatocytes in the liver (Please see Supplementary Figure S1 available online at http://ebm.rsmjournals.com/ lookup/suppl/doi:10.1258/ebm.2012.012135/-/DC1), while in the lung it was mainly detected in the cytoplasm of inflammatory cells (mainly macrophages). 25 Mice were maintained under a 12 h light/dark cycle at 218C + 18C and bred at the Animal Care Facility of the Experimental Surgery Division of the University of Padua. In preliminary experiments, to assess the optimal dose to induce ALF, a group of 10 mice (5 transgenic and 5 wildtype) were inoculated intraperitoneally with increasing concentrations of acetaminophen and a concentration of 0.8 mg/g body weight was chosen for further experiments.…”
Section: Methodsmentioning
confidence: 99%